Legal Consequences of the Judgment in Domestic Violence Cases: A Study of Islamic Family Law - Nabiila Surya Arifin; Shely Nasya Putri (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
This article discusses the legal consequences of domestic violence (DV) decisions, specifically the Metro District Court Decision Number 18/PID.SUS/2022/PN.MET. The issue examined is how the legal system handles domestic violence, focusing on the framework of Indonesian positive law and Islamic Family Law. The main problem encountered is the gap between the sanctions imposed on perpetrators and the protection and restitution received by victims. The purpose of this study is to analyze the legal consequences of this decision from an Indonesian legal perspective, specifically Law No. 23 of 2004 concerning the Elimination of Domestic Violence, and to assess its compliance with the principles of Islamic Family Law, which emphasize justice and the protection of victims' rights. The theory used in this study encompasses positive law and Islamic family law principles, with the research method used being normative legal research combined with content analysis of court decisions. The research findings indicate that this decision imposes minimal penalties on perpetrators and does not provide adequate restitution or psychological rehabilitation for victims. The recommendation given is a more comprehensive approach by combining the criminal and civil legal frameworks, and integrating the concepts of ta'zir and dharar from Islamic law to ensure protection and justice for victims of domestic violence.